2005
DOI: 10.1116/1.2073468
|View full text |Cite
|
Sign up to set email alerts
|

Etching characteristics of high-k dielectric HfO2 thin films in inductively coupled fluorocarbon plasmas

Abstract: Formation of polycrystalline silicon germanium/HfO 2 gate stack structure using inductively coupled plasma etching J.Inductively coupled fluorocarbon ͑CF 4 / Ar and C 4 F 8 /Ar͒ plasmas were used to etch HfO 2 , which is a promising high-dielectric-constant material for the gate of complementary metal-oxide-semiconductor devices. The etch rates of HfO 2 in CF 4 / Ar plasmas exceeded those in C 4 F 8 / Ar plasmas. The tendency for etch rates to become higher in fluorine-rich ͑high F / C ratio͒ conditions indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Furthermore, the ion energy in a conventional plasma reactor is not very well defined and often has a bimodal energy distribution due to the applied radio frequency voltage. 32 These effects might explain why not all etch rate data 4,5,8,9 agree well with Eq. ͑2͒, while the etch yield may still follow this ion energy dependence.…”
Section: ͑2͒supporting
confidence: 54%
See 2 more Smart Citations
“…Furthermore, the ion energy in a conventional plasma reactor is not very well defined and often has a bimodal energy distribution due to the applied radio frequency voltage. 32 These effects might explain why not all etch rate data 4,5,8,9 agree well with Eq. ͑2͒, while the etch yield may still follow this ion energy dependence.…”
Section: ͑2͒supporting
confidence: 54%
“…A wide variety of chemistries have been tried for the etching of high-k metal oxides such as HfO 2 and ZrO 2 . [4][5][6][7][8][9][10][11][12] These studies have revealed that etching of these materials is dominated by momentum transfer from the ions to the surface atoms in most cases. [7][8][9] An etch selectivity toward Si of 10 and higher has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, after etch a lot of non-volatile etch products (fluorides) were observed on the surface. 9 , 10 One can conclude that fluorine can break a metal-oxygen bond and a form a fluoride, but these fluorides are usually not volatile enough to be removed from the surface. Another concern for the fluorine-based chemistry is selectivity over the substrate.…”
Section: Dry Removalmentioning
confidence: 99%
“…Currently, there are many published works on the investigation of the HfO 2 etch process in fluorinebased, [3][4][5][6][7][8][9] chlorine-based, 3 6 7 9−12 bromine-based 6 10 13 and hydrogen-based 3 gas chemistries. The results of these works can be summarised as follows: (1) The chemical enhancement of the HfO 2 etching rate over the pure ion etching in Ar plasma is maximum for the Cl-and Br-based gas chemisties and minimum for the fluorine-based ones.…”
Section: Introductionmentioning
confidence: 99%